2022
DOI: 10.3847/psj/ac69eb
|View full text |Cite
|
Sign up to set email alerts
|

Mid-ultraviolet Hubble Observations of Europa and the Global Surface Distribution of SO2

Abstract: We present spatially resolved reflectance spectra of Europa’s surface in the wavelength range of 210–315 nm obtained by the Hubble Space Telescope Imaging Spectrograph in 2018 and 2019. These data provide the first high-quality, near-global spectral observations of Europa from 210 to 240 nm. They show that the reflectance of Europa’s leading, trailing, anti-Jovian, and sub-Jovian hemispheres is ∼5% near 210 nm, with varying spectral slopes across the mid-UV. This low albedo, even on the more “pristine” leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…However, the lack of detection of O 3 on Europa is a bit more puzzling, as laboratory studies have shown that O 3 is easily produced from ion and electron irradiation of O 2 ice (Famá et al 2002;Bennett & Kaiser 2005) and heavy ion irradiation of H 2 O ice that is deposited while being actively irradiated (Teolis et al 2006). While it is unclear why O 3 is absent on the leading hemisphere of Europa, we have noted previously that the lack of O 3 on the trailing hemisphere of Europa could be due to thermal reactions with SO 2 (Loeffler & Hudson 2016), which has been detected previously (Lane et al 1981;Hendrix et al 2011;Becker et al 2022). Here we show that H 2 S will also react with O 3 on the order of hours or days at the temperatures found on Europa (∼90-130 K).…”
Section: Astrophysical Implicationsmentioning
confidence: 61%
“…However, the lack of detection of O 3 on Europa is a bit more puzzling, as laboratory studies have shown that O 3 is easily produced from ion and electron irradiation of O 2 ice (Famá et al 2002;Bennett & Kaiser 2005) and heavy ion irradiation of H 2 O ice that is deposited while being actively irradiated (Teolis et al 2006). While it is unclear why O 3 is absent on the leading hemisphere of Europa, we have noted previously that the lack of O 3 on the trailing hemisphere of Europa could be due to thermal reactions with SO 2 (Loeffler & Hudson 2016), which has been detected previously (Lane et al 1981;Hendrix et al 2011;Becker et al 2022). Here we show that H 2 S will also react with O 3 on the order of hours or days at the temperatures found on Europa (∼90-130 K).…”
Section: Astrophysical Implicationsmentioning
confidence: 61%
“…Therefore, it is reasonable to suggest that the implantation of sulfur ions into the Europan H 2 O surface ices yields H 2 SO 4 hydrates (Ding et al, 2013;Strazzulla et al, 2007Strazzulla et al, , 2009, which are then dissociated to yield SO 2 upon further irradiation. It is also possible that alternative formation mechanisms, such as the radiolytic decomposition of sulfate minerals (McCord et al, 2001) and the implantation of cold (sub-keV) magnetospheric sulfur ions into the Europan surface ice (Becker et al, 2022), may further contribute to the presence of SO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The detection of SO2 ice on the trailing hemisphere of Europa by the International Ultraviolet Explorer spacecraft (Lane et al 1981) led many researchers to suggest that an influx of magnetospheric sulphur ions could contribute to its formation there as part of a wider radiolytic sulphur cycle (Carlson et al 1999), in which sulphur is chemically transformed to various molecular forms as a result of its interaction with ionising radiation. Indeed, the distribution of SO2 on the Europan trailing hemisphere is such that it adopts a so-called bulls-eye pattern (Carlson et al 2005, Hendrix et al 2011, Becker et al 2022. This is suggestive of an exogenic sulphur source in which magnetospheric sulphur ions implanting into the surface ices yield SO2 as a primary product.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On Europa, it is possible that underlying ice abundance (relative to non-ice materials) is responsible for this dichotomy (21,66), as we suggest may be the case for Ganymede. Another possibility is that SO 2 (72)(73)(74) formed as a result of the preferential sulfur bombardment of Europa's trailing hemisphere (67) acts to deplete H 2 O 2 via thermal reactions that produce sulfate (75). However, while similar reactions warrant consideration for Ganymede, they may present a less viable mechanism for its trailing hemisphere, as models suggest that Ganymede's intrinsic magnetic field should direct most of the impinging sulfur ions to the high latitudes of both hemispheres (13,61).…”
Section: Discussionmentioning
confidence: 99%